Predictors of Booster Response to Hepatitis B Vaccine at 15 years of age: A Cross-Sectional School-Based Study - Yu-Sheng Chen; Chia-Hsiang Chu; Jen-Hung Wang; Jun-Song Lin; Yung-Chieh Chang (Elsevier, 2016)
The current consensus does not support the use of booster dose because of its anamnestic response in almost all children 15 years after universal infant hepatitis B virus (HBV) vaccination. However, in our clinical setting, numerous concerned parents request a booster administration for their children. We aimed to provide the possible predictors of booster response in adolescents before this booster administration. Methods: This study comprised a series of cross-sectional serological surveys of HBV markers in 15-year-old individuals between 2008 and 2012. Data on serum hepatitis B surface antigen, hepatitis B surface antibody (anti-HBs), and liver-function biomarkers in a total of 887 senior high-school students were collected. There were two parts to this study: HBV seroepidemiology and booster-response analysis to identify the possible response predictors and decay factors after the HBV booster administration. Results: The overall anti-HBs and hepatitis B surface antigen seropositivity rates were 34.7% and 0.7%, respectively, and the median anti-HBs titer was 3.3 mIU/mL. Six weeks after one dose of recombinant HBV vaccine, the overall booster-response rate in the double-seronegative recipients was 94% (471/501). Among the participants whose initial anti-HBs titers were undetectable or low, 72.4% (247/341) and 95.6% (153/160), respectively, reactivated their anti-HBs titers ≥ 100 mIU/mL about 6 weeks after the booster administration. The likelihood of postbooster anti-HBs titer reaching an adequate protective level increased with the prebooster titer. The female participants had stronger anamnestic responses compared to the male participants. Conclusion: We found that the female participants and prebooster anti-HBs titers above the detection limit of the immunoassay were good predictors of HBV booster response.